Common myths among a group of Iranian women concerning sexual relationships during pregnancy - Shojaa, Mahdieh; Jouybari, Leila M.; Sanagoo, Akram (Archives of Medical Science, 2009)
Introduction: There are a variety of ideas and beliefs among women about sexual relationships during pregnancy. The aim of the study was to discover the beliefs of pregnant women about having sex during pregnancy. Material and methods: Open-ended interviews were conducted with 51 pregnant women who were referred to the teaching clinic in Iran. All of the interviews were tape recorded and transcribed line by line. The data were coded and categorized as is usual in qualitative methods. Results: Two main themes in the study are “Anxious of harmfulness” and “Feeling sinful”. Fear of abortion, fetus suffocation, fetus abnormality, rupture of fetus hymen, and concern of harm to the mother are some of the myths among our participants. Conclusions: Since some of the beliefs are harmful and could have a negative impact on relationships, the role of evidence-based education in providing a healthy sex life should be considered.